HR COMPETENCY USING THE MODEL OF PEOPLE CAPABILITY MATURITY AND ITS IMPACT ON HR COMPETITIVE ADVANTAGE - Widyawati, Sapta; Landra, Nengah; Novarini, Ni Nyoman Ari (Jurnal Riset Bisnis dan Manajemen, 2026)
The purpose of establishing a company is to operate over an extended period, so company should have ability in competing. The competitiveness of a company can be captured by prioritizing the competitive advantage of human resources (HR), because HR is a key resource in a company. However, in reality the competitive advantage of HR is still relatively weak. This study aims to analyze human resource (HR) competency using the Model of People Capability Maturity (PCM) to determine its impact on HR competitive advantage. The research sample was 426 respondents who were taken using a quota sampling technique from a population of employees at three networked companies in Bali. The analysis technique uses linear regression analysis with SPSS v.23 application. Human resource competencies based on the model of Model of PCM significantly influence the competitive advantage of human resources, with four components, namely: strategic partner, administrative expert, employee champion, and change agent.